2017
DOI: 10.1371/journal.pone.0184649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tramadol as an adjuvant to local anesthetics for brachial plexus block: A systematic review and meta-analysis

Abstract: BackgroundTramadol, a 4-phenyl-piperidine analog of codeine, has a unique action in that it has a central opioidergic, noradrenergic, serotonergic analgesic, and peripheral local anesthetic (LA) effect. Many studies have reported contradictory findings regarding the peripheral analgesic effect of tramadol as an adjuvant to LA in brachial plexus block (BPB). This meta-analysis aimed to evaluate the effects of tramadol as an adjunct to LA in BPB during shoulder or upper extremity surgery.MethodsWe searched the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
2
22
0
2
Order By: Relevance
“…Two systematic reviews also ended up with different conclusions and recommendations [8,9]. The first, based on eight studies, suggested that patients undergoing surgery under brachial plexus block will not benefit from tramadol added as adjuvant as there is lack of effectiveness to prolong analgesia; additionally, the potential of neurotoxicity of tramadol when injected perineurally cannot be excluded [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two systematic reviews also ended up with different conclusions and recommendations [8,9]. The first, based on eight studies, suggested that patients undergoing surgery under brachial plexus block will not benefit from tramadol added as adjuvant as there is lack of effectiveness to prolong analgesia; additionally, the potential of neurotoxicity of tramadol when injected perineurally cannot be excluded [8].…”
Section: Discussionmentioning
confidence: 99%
“…The first, based on eight studies, suggested that patients undergoing surgery under brachial plexus block will not benefit from tramadol added as adjuvant as there is lack of effectiveness to prolong analgesia; additionally, the potential of neurotoxicity of tramadol when injected perineurally cannot be excluded [8]. In contrast, the second review and meta-analysis that included 16 randomized control studies and 751 patients showed that 100 mg but not 50 mg tramadol as adjuvant prolonged the duration of the sensory and motor blocks, and eventually prolonged postoperative analgesia with no impact on adverse effects [9]. The onset of sensory and motor blocks was also enhanced [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachial plexus block (BPB) is now a widely used technique adopted by anesthesiologist for surgeries involving the upper limb and for acute pain management. 2 BPB is advantageous when compared with general anesthesia, because it provides better pain control, no side effects as with general anesthesia and llonger control of post-op pain. 3 However, the duration of block is only 8 hours to 14 hours even with the use of longer half-life local anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many adjuvants have been searched to extend the analgesic efficacy and to reduce adverse outcomes of local anesthesia such as perineural magnesium, dexmedetomidine, clonidine, dexamethasone and tramadol. 2,[5][6][7][8] Use of tramadol as oral or parenteral is now proven effective for post-op management of pain. 9 Tramadol minimizes pain using two different pathways; opioid like action mediated by action of μ receptors and 2 nd one mediated by its α 2 -adrenergic and serotoninergic activity.…”
Section: Introductionmentioning
confidence: 99%